Posisi Santri Perempuan di Pesantren dalam Perspektif Gender: Studi Kasus PP. Krapyak Yogyakarta - Azzahra, Mauly Khalwa (Jujurnal Publisher, 2024)
This study examines the position of female students at the Krapyak Islamic Boarding School in Yogyakarta, a modern Islamic boarding school that maintains traditional values, using a descriptive qualitative approach through interviews, observation, and documentation. The analysis is conducted through Mansour Fakih's gender perspective, which distinguishes sex as a biological nature from gender as a social construct, and identifies five forms of gender inequality: marginalization, subordination, stereotyping, double workload, and violence. The research focuses on four dimensions: access to education, leadership participation, division of socio-domestic roles, and gender awareness. The results indicate that the Krapyak Islamic Boarding School has provided relatively equal access to education and leadership space for male and female students, divided socio-domestic roles more equitably, and fostered gender awareness through gender interpretation studies and career mentoring programs. Although patriarchal bias is still found in some aspects, the position of female students at this Islamic boarding school is generally moving towards equality.